Satureja kermanica (Lamiaceae) a new species from south-east of Iran, inferred from molecular and morphological evidence - Bordbar, Firouzeh; Payandeh, Maryam; Mirtadzadini, Mansour (Phytotaxa, 2020)
Traditional morphometric and multivariate analyses on relevant traits were carried out on populations identified as S. bachtiarica throughout the distribution range in Iran. This was complemented by molecular phylogenetic analysis of nuclear rDNA sequences (ITS). Based on these results the SE populations are described as a new species, Satureja kermanica sp. nov. The new taxon is illustrated and compared to its close relatives. The new species is distinguished from S. bachtiarica by several qualitative and quantitative characters: the length of internodes, the state of stem indumentum, the color of corolla, the shape and the length of calyx, the ratio of the length of lower to the length of upper calyx teeth, the ratio of calyx length to the lower teeth length, the length of stamens and the style. The new species is geographically isolated and restricted to the Irano-Turanian floristic region of Kerman Province. It preferably grows on the gravelly sediments of seasonal streams. Due to its restricted occurrence, the species is considered endangered (EN) according to IUCN criteria.